Effect of Selected Bacteria as Bioremediation on the Degradation of Fats Oils and Greases in Wastewater from Cafeteria Grease Traps - Lauprasert, Prachumporn; Chansirirattana, Jessada; Paengjan, Jenjira (European Journal of Sustainable Development, 2017)
Fats, oils and greases (FOG) are used in the food preparation and cooking. However, FOG are pouring an accumulative load on drainage systems as they can cause blockages. They also can pollute public sewer systems and can deplete oxygen levels in waterways causing aquatic life may be killed. The objectives of this research were to study the activity of immobilized enzyme lipase derived from the selected bacteria; Bacillus subtilis, Staphylococcus epidermidis, and Pseudomonas aeruginosa on FOG degradation and wastewater treatment in cafeteria grease traps. The experiment data collected after bacterial cultivation in the wastewater for 5 days. The comparison between batch and continuous methods was investigated. The results show that activities of enzyme lipase in oily wastewater using continuous method showed the high efficacy more than batch method. The most activity of enzyme lipase was found in P. aeruginosa to be 819.92 unit/ ml. significantly (p < 0.001), following by B. subtilis and S. epidermidis to be 579.95 and 559.95 unit/ ml, respectively. Moreover, the most thickness reduction of the fat layer was found in P. aeruginosa to be 61.22 percent significantly (p < 0.05), following by B. subtilis and S. epidermidis to be 57.14 and 53.06 percent, respectively. Nevertheless, the most BOD5 treatment efficiency was found in B. subtilis to be 64.51 percent removal, following by S. epidermidis and P. aeruginosa to be 63.58 and 60.72 percent, respectively. In conclusions, enzyme lipase from P. aeruginosa show that the most thickness reduction of the fat layer using continuous method. However, B. subtilis reduced the BOD5 to a minimum by continuous method. This bioremediation method would increase efficiency of oily wastewater and FOG degradation, moreover, this method could minimize area disturbance compared with physical and chemical method. Keywords: Bioremediation, immobilized enzyme lipase, degradation of FOG in Wastewater, reduced the thickness of the fat layer